Safety, Pharmacokinetics, Pharmacodynamics, and Antitumor Activity of Necuparanib Combined with Nab‐Paclitaxel and Gemcitabine in Patients with Metastatic Pancreatic Cancer: Phase I Results. (4th December 2017) - O'Reilly, Eileen M.; Roach, James; Miller, Paul; Yu, Kenneth H.; Tjan, Catherine; Rosano, Molly; Krause, Silva; Avery, William; Wolf, Julie; Flaherty, Keith; Nix, Darrell; Ryan, David P.
Abstract: Lessons Learned: Despite the compelling preclinical rationale of evaluating the genetically engineered heparin derivative, necuparanib, combined with standard therapy in metastatic pancreas adenocarcinoma, the results were ultimately disappointing. Safety was documented, although dose escalation was limited by the number of subcutaneous injections, the potential for skin toxicity (cellulitis), and low‐level anticoagulant effect. Nonetheless, the hypothesis of targeting prothrombotic pathways in pancreas adenocarcinoma remains compelling. Background: Necuparanib is derived from unfractionated heparin and engineered for reduced anticoagulant activity while preserving known heparin‐associated antitumor properties. This trial assessed the safety, pharmacokinetics (PK), pharmacodynamics, and initial efficacy of necuparanib combined with gemcitabine ± nab‐paclitaxel in patients with metastatic pancreatic cancer. Methods: Patients received escalating daily subcutaneous doses of necuparanib plus 1, 000 mg/m 2 gemcitabine (days 1, 8, 15, and every 28 days). The protocol was amended to include 125 mg/m 2 nab‐paclitaxel after two cohorts (following release of the phase III MPACT data). The necuparanib starting dose was 0.5 mg/kg, with escalation via a modified 3 + 3 design until the maximum tolerated dose (MTD) was determined. Results: Thirty‐nine patients were enrolled into seven cohorts (necuparanib 0.5, 1 mg/kg + gemcitabine; necuparanib 1, 2, 4, 6, and 5 mg/kg + nab‐paclitaxel + gemcitabine). The most common adverse events were anemia (56%), fatigue (51%), neutropenia (51%), leukopenia (41%), and thrombocytopenia (41%). No deaths and two serious adverse events were potentially related to necuparanib. Measurable levels of necuparanib were seen starting at the 2 mg/kg dose. Of 24 patients who received at least one dose of necuparanib + nab‐paclitaxel + gemcitabine, 9 (38%) achieved a partial response and 6 (25%) achieved stable disease (63% disease control rate). Given a cellulitis event and mild activated partial thromboplastin time increases at 6 mg/kg, the 5 mg/kg dose was considered the MTD and selected for further assessment in phase II. Conclusion: Acceptable safety and encouraging signals of activity in patients with metastatic pancreatic cancer receiving necuparanib, nab‐paclitaxel, and gemcitabine were demonstrated. Abstract : 摘要 背景 . Necuparanib是普通肝素的衍生物, 经基因改造为在保留已知肝素相关抗肿瘤特性的同时降低抗凝血活性。本试验评估了necuparanib联合吉西他滨±白蛋白结合型紫杉醇治疗转移性胰腺癌患者的安全性、药代动力学（PK）、药效学和初始疗效。 材料与方法 . 患者每天接受剂量递增的necuparanib皮下注射+吉西他滨1, 000 mg/m 2 （第1、8和15天, 28天一个周期）。在两个队列后对方案进行了修订, 纳入白蛋白结合型紫杉醇125 mg/m 2 （发布III期MPACT数据之后）。Necuparanib的起始剂量为0.5mg/kg, 通过修订后的3 + 3设计进行剂量递增, 直至确定最大耐受剂量（MTD）。 结果 . 39例患者入组进入7个队列（necuparanib 0.5, 1 mg/kg +吉西他滨；necuparanib 1, 2, 4, 6和5 mg/kg +白蛋白结合型紫杉醇+吉西他滨）。最常见的不良事件为贫血（56%）、疲乏（51%）、中性粒细胞减少症（51%）、白细胞减少症（41%）和血小板减少症（41%）。研究期间发生了两起可能与necuparanib有关的严重不良事件, 未发生死亡事件。从2 mg/kg剂量水平开始可检出necuparanib。在至少接受了1次necuparanib+白蛋白结合型紫杉醇+吉西他滨给药的24例患者中, 9例（38%）患者达到部分缓解, 6例（25%）达到疾病稳定（63%疾病控制率）。由于6 mg/kg剂量水平下发生蜂窝织炎事件和活化部分凝血活酶时间轻度延长, 判定5 mg/kg剂量水平为MTD并且将在II期研究中对其进行进一步评估。 结论 . 研究证实接受necuparanib、白蛋白结合型紫杉醇和吉西他滨治疗的转移性胰腺癌患者的安全性可接受且活性较好。